Fundamentals of anatomy & physiology - Frederic H. Martini
This book covers information basic to understanding anatomy and physiology as taught in a traditional two-semester course. The purpose of the book is to give readers a strong foundation in fundamental concepts and science before they attempt a course in Anatomy and Physiology. This book is specifically designed for an Anatomy and Physiology preparation course which focuses on inorganic and organic chemistry, the structure and function of cells, tissues, development and inheritance. For instructors and students, or anyone interested in the fundamentals of anatomy and physiology.